Potential of Natural Regeneration Mangrove Seedling on The Coast of Davi Village Biak Numfor Regency, Papua - Manan, Jemmy; Manumpil, Abraham W.; Asaribab, Pilipus Y.; Saleky, Dandi (Sam Ratulangi University, 2021)
Mangrove ecosystem is an important ecosystem in coastal areas which is a habitat for various types of organisms. The existence of mangrove ecosystems in nature is strongly influenced by the availability of mangrove seedlings and seedlings because they are closely related to the secondary succession process in natural habitats. This research was conducted to analyze the potential for regeneration of mangrove seedlings in the coastal area of Dafi Village, Biak Numfor Regency, Papua. Data collection on the potential for regeneration of mangrove seedlings was carried out using the belt transect method. Analysis of species composition and structure of mangrove vegetation at the seedling level used analysis of species density, relative density, species frequency, relative frequency, and important value index. A total of seven mangrove species were found in the coastal area of Dafi Village, Biak Numfor Regency, consisting of Bruguiera gymnorrhiza, Bruguiera cylindrica, Ceriops Tagal, Rhizophora apiculata, Rhizophora mucronata, Rhizophora Stylosa, and Lumnitzera racemoza. The highest species density and relative density values were found in Bruguiera gymnorrizha and Cerops tagal, while the lowest was Rhizophora mucronata and Lumnitzera racemoza. The highest value of species frequency and relative frequency was Bruguiera gymnorrizha, while the lowest was Rhizophora mucronata. The highest Importance Value Index (INP) of mangrove seedlings was found in Ceriops tagal and Bruguiera gymnorrizha, while Rhizophora mucronata had the lowest INP compared to other species.Keywords: Mangrove Ecosystem; Mangrove Regeneration; Important Value Index AbstrakEkosistem mangrove merupakan ekosistem penting di wilayah pesisir yang menjadi habitat bagi berbagai jenis organisme. Keberadaan ekosistem mangrove dialam sangat dipengaruhi oleh ketersediaan anakan dan semai mangrove, karena sangat berkaitan erat dengan proses suksesi sekunder pada habitat alami. Penelitian ini dilakukan dengan tujuan menganalisis potensi regenerasi semai mangrove di Pesisir Kampung Dafi Kabupaten Biak Numfor Papua. Pengumpulan data potensi regenerasi semai mangrove dilakukan dengan menggunakan metode belt transek. Analisis komposisi jenis dan struktur vegetasi mangrove tingkat semai menggunakan analisis kerapatan jenis, kerapatan relatif, frekuensi jenis, frekuensi relatif, dan indeks nilai penting. Total tujuh jenis mangrove ditemukan di Pesisir Kampung Dafi Kabupaten Biak Numfor yang terdiri atas jenis Bruguiera gymnorrhiza, Bruguiera cylindrica, Ceriops Tagal, Rhizophora apiculata, Rhizophora mucronata, Rhizophora Stylosa, dan Lumnitzera racemoza. Nilai kerapatan jenis dan kerapatan relatif tertinggi ditemukan pada jenis Bruguiera gymnorrizha dan Cerops tagal, sedangkan terrendah adalah jenis Rhizophora mucronata dan Lumnitzera racemoza. Nilai frekuensi jenis dan frekuensi relatif tertinggi adalah jenis Bruguiera gymnorrizha sedangkan yang terendah adalah jenis Rhizophora mucronata. Indeks Nilai Penting (INP) semai mangrove tertinggi ditemukan pada jenis Ceriops tagal dan Bruguiera gymnorrizha sedangkan jenis Rhizophora mucronata memiliki INP terrendah dibanding jenis lainnya.Kata kunci: Ekosistem Mangrove; Regenerasi Mangrove; Indeks Nilai Penting